Kemampuan representasi matematis pada materi bangun ruang sisi datar: Model problem based learning - Rasyidin, Muhammad Irhas; Minarti, Eva Dwi; Yuspriyati, Devi Nurul (IKIP Siliwangi, 2024)
The research aims to investigate the achievement of students' mathematical representation abilities in the material of flat-sided space after receiving a problem-based learning model. This study employs a quasi-experimental method with a non-equivalent control group design, as there is no randomization of samples in both classes. The population consists of eighth-grade students at SMP Dharma Kartini, with the research sample being class VIII-A as the control group and class VIII-B as the experimental group, each consisting of 35 students. The instruments and learning tools used include pretest and posttest questions, as well as LKPD containing material on flat-sided space and the stages of the PBL model. The obtained data will be processed using statistical tests through a two-sample independent t-test, preceded by a normality test and followed by the Mann-Whitney test. The results of the study interpret that there is a difference in the achievement of students' mathematical representation abilities after the PBL model is applied to the flat-sided space material.